Nanopore-based amplicon sequencing for rapid detection and identification of Bacillus spp. in plant-based products - Bisaschi, Marta; Bellassi, Paolo; Fontana, Alessandra; Callegari, Maria Luisa; Bourdichon, François; Del Casale, Antonio; Fracchetti, Fabio; Morelli, Lorenzo; Patrone, Vania (Frontiers in Microbiology, 2025)
Bacillus contamination in plant-based food products is a significant concern due to heat-resistant spores that can survive heating and proliferate during storage or handling, possibly leading to foodborne illnesses. Given the potential of high-throughput DNA sequencing to enhance microbial monitoring, we used a targeted approach by combining amplification of the Bacillus tuf gene with Oxford Nanopore sequencing. The ability of the MinION-based protocol to detect and identify closely related Bacillus species was first assessed using plant-based food samples spiked with spore suspensions of five representative Bacillus strains. A DNA extraction method, relying on food enzymatic pre-processing combined with mechanical cell lysis, was implemented to maximize Bacillus spore DNA recovery, and a droplet digital PCR (ddPCR) assay was used to evaluate extraction efficiency. Afterwards, the approach was applied to 72 different commercial plant-based foods and supplements to compare nanopore-based tuf profiling with established nanopore-based 16S rRNA analysis and culture-based methods. ddPCR analysis showed the high efficiency of the DNA extraction procedure for Bacillus spores from spiked samples. Sequencing of the tuf gene with the MinION device successfully differentiated the five different Bacillus species selected as reference strains for the artificial inoculation of food, when the resulting sequences were aligned against the custom-made BacTufDB database. Tests on commercial products confirmed the tuf gene ability (over the 16S rRNA gene) to highlight the presence of Bacillus species: Bacillus and closely related genera were detected in 35 of the tested plant-based products, out of which seven were contaminated by Bacillus cereus group. The study demonstrated that the tuf-based methodology more effectively detects Bacillus species in plant-based products, offering potential applications in food safety and quality control.